1997
DOI: 10.1136/jcp.50.9.790
|View full text |Cite
|
Sign up to set email alerts
|

Screening for bacterial vaginosis: a novel application of artificial nose technology.

Abstract: The AromaScan system was used to analyse vaginal swabs from 68 women attending a genitourinary clinic. Using clinical criteria, subjects were assessed for bacterial vaginosis. After training the AromaScan system to recognise patterns generated from four patients with and four patients without bacterial vaginosis, 16 of the 17 (94%) remaining subjects were correctly identified as having the condition. The positive predictive value of the test was 61.5%. These results indicate that the AromaScan technology may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…128 (2) The screening for bacterial vaginosis in vaginal swabs seems to be feasible. 129 Newer publications even give the impression that the reliability is comparable to that of present tests and show the possibility of controlling treatment of bacterial vaginosis by tracking the acetic acid concentration with a conducting polymer array. 130,131 (3) Common bacterial pathogens of the upper respiratory tract were obtained from in vitro samples and successfully detected by a Cyranose 320 electronic nose.…”
Section: Disease Diagnosismentioning
confidence: 76%
“…128 (2) The screening for bacterial vaginosis in vaginal swabs seems to be feasible. 129 Newer publications even give the impression that the reliability is comparable to that of present tests and show the possibility of controlling treatment of bacterial vaginosis by tracking the acetic acid concentration with a conducting polymer array. 130,131 (3) Common bacterial pathogens of the upper respiratory tract were obtained from in vitro samples and successfully detected by a Cyranose 320 electronic nose.…”
Section: Disease Diagnosismentioning
confidence: 76%
“…The metabolites are detected with an array of conducting polymer gas sensors which undergo changes in resistance on exposure to specific gases (5,10,20,24,26). Work conducted by Chandiok et al (4) first demonstrated the possibility of using conducting polymer gas sensor arrays for the diagnosis of BV.…”
mentioning
confidence: 99%
“…Chandiok et al [10] first demonstrated the possibility of using conducting polymer gas sensor arrays for detecting BV. Subsequent work using headspace-gas chromatography-mass spectrometry (HS-GC-MS) demonstrated that acetic acid was the primary volatile compound produced from vaginal swabs and further studies using Osmetechs system have demonstrated its clinical utility [11].…”
Section: Bacterial Vaginosis (Bv)mentioning
confidence: 99%